Sticks or Carrots? Comparing Effectiveness of Government Informal Economy Policies in Russia. Issue 4 (December 2018) - Kluge, Janis; Libman, Alexander
Abstract Which incentives have the strongest impact on the size of the informal economy? Is it about government's pressure against entrepreneurs operating in this sector, or is it about the benefits of legality? The goal of this paper is to explicitly contrast the role ofsticks (court repressiveness) andcarrots (financial aid to small- and medium-sized firms) as factors determining the size of the informal economy, using the case of the Russian taxi market. It uses a unique dataset of taxi licensing data from regional transport departments and indicators for taxi market demand and supply to estimate the extent of informal business. When controlling for market demand and supply, it finds a strong and robust positive effect of sanctions on the size of the official market, with higher repressiveness leading to a smaller informal economy. In contrast, the effect ofcarrots was insignificant. The results suggest that the effectiveness ofcarrot policies is compromised when entrepreneurs operate informally to avoid dealing with corrupt bureaucrats and have low trust in the government.